Should we offer multi-gene testing to all patients with breast cancer: a cost-effectiveness analysis. (1st November 2019) - Sun, L; Brentnall, A; Patel, S; Buist, D; Bowles, E; Evans, DG; Eccles, D; Hopper, J; Li, S; Duffy, S; Cuzick, J; dos-Santos-Silva, I; et al.
Abstract : Introduction/Background: Currently breast cancer (BC) patients are offered genetic-testing only if they have a ≥10% risk of being a BRCA carrier based on family history and clinical criteria. However, this approach misses a large proportion (∼50%) of overall mutation carriers as they fall below this 10% threshold. Mutation identification enables primary prevention for ovarian cancer (OC) in BC-patients and BC-&-OC in unaffected relatives. We estimate incremental lifetime-effects, costs, cost-effectiveness and population impact of multigene-testing all BC patients compared to current practice of family-history/clinical-criteria based genetic ( BRCA )-testing. Methodology: Cost-effectiveness microsimulation modelling study comparing lifetime costs-&-effects of BRCA1/BRCA2/PALB2 (multigene) testing all unselected BC-cases (Strategy-A) with family-history/clinical-criteria based BRCA1/BRCA2 -testing (Strategy-B) in both UK and US populations. Data obtained from 11, 836 population-based BC-patients (regardless of family-history) recruited to four large research studies in the UK (Predicting-Risk-of-Breast-Cancer-at-Screening (PROCAS: 1389 out of 57, 000 women) & Prospective-Outcomes-in-Sporadic-versus-Hereditary-breast-cancer (POSH: 2885) studies); US (Kaiser-Permanente Washington Breast-Cancer-Surveillance-Consortium (BCSC) registry: 5892 out of 132, 139 women) and Australia (Population-based BC-cases of the Australian-Breast-Cancer-Family-Study (ABCFS: 1670 women)). The main outcome measure was the incremental cost per quality-adjusted life-year (QALY) gained with a 3.5% annual discount. Parameter uncertainty was explored using one-way and probabilistic sensitivity analyses. Results: Compared with current clinical-criteria/family-history-based BRCA -testing, ( BRCA1/BRCA2/PALB2 ) multigene-testing for all BC-patients would cost £10, 470/QALY (UK) or $58, 702/QALY (US) gained, well below UK/NICE and US cost-effectiveness thresholds of £30, 000/QALY & $100, 000/QALY. Probabilistic sensitivity-analysis shows unselected multigene-testing remains cost-effective for 98% UK/77% US health-system simulations. One year's unselected panel-genetic testing can prevent 1, 776 BC/OC-cases and 557 deaths in the UK; and 8, 258 BC/OC-cases and 2, 143 deaths in the US. Correspondingly, 7 UK/32 US excess heart-disease deaths occur annually. Conclusion: Unselected panel genetic-testing for all BC patients compared to current clinical-criteria restricted testing is extremely cost-effective. We recommend changing the current policy to expand genetic testing to all BC patients. Disclosure: RM declares research funding from The Eve Appeal and Cancer Research UK into population testing and from Barts & the London Charity and Rosetree Charity outside this work, as well as an honorarium for grant review from Israel National Institute for Health Policy Research and honorarium for advisory board meeting for MSD and Astrazeneca. DGE declares travel grants paid by Astrazeneca. The other authors declare no conflict of interest.